Carboxymethyl Cellulose-Stabilized Platinum Nanoparticles Synthesized by Pulsed Laser Ablation for Enhanced CT Scan Contrast - Wahyuddin, Wahyuddin; Jonathan, Felix; Hidayanto, Eko; Khumaeni, Ali (Diponegoro University Semarang Indonesia, 2025)
This study demonstrates the performance of platinum nanoparticles (Pt NPs) as contrast agents for computed tomography (CT). Synthesized through pulsed laser ablation, Pt NPs were stabilized in carboxymethyl cellulose (CMC). In CT imaging evaluations, the CMC-stabilized Pt NPs generated significantly higher Hounsfield Unit (HU) values and contrast-to-noise ratio (CNR) than both their DIW-based counterparts and a conventional iodine-based agent. Remarkably, this enhanced contrast was achieved at substantially lower ppm concentrations, highlighting the potential of CMC-stabilized Pt NPs to offer a more efficient and powerful alternative to current clinical standards.